02 Intro Quantifiers - Handout
02 Intro Quantifiers - Handout
02 Intro Quantifiers - Handout
Lecture 2: Quantifiers
Jittat Fakcharoenphol
P Q P ∧Q P ∨Q ¬P
T T T T F
T F F T
F T F T T
F F F F
Quick check 1
P ¬P P ∧ ¬P P ∨ ¬P
T F F T
F T F T
P ⇒Q
P Q P ⇒Q
T T T
T F F
F T T
F F T
1
Materials in this lecture are mostly from Berkeley CS70’s lecture notes.
What?
I Note that this statement does not say anything about the case
when P is false, i.e., it only considers the case when P is true.
I Therefore, having that P ⇒ Q is true is OK with the case
that (1) Q is false when P is false, and (2) Q is true when P
is false.
I This is an example when mathematical language is “stricter”
than natural language.
Noticing if-then
We can write “if P , then Q” for P ⇒ Q, but there are other ways
to say this. E.g., we can write (1) Q if P , (2) P only if Q, or (3)
when P , then Q.
Quick check 2
For each of these statements, define propositional variables
representing each proposition inside the statement and write
the proposition form of the statement.
I If you do not have enough sleep, you will feel dizzy
during class.
I If you eat a lot and you do not have enough exercise,
you will get fat.
I You can get A from this course, only if you work fairly
hard.
Only-if
P Q R
T T
T F
F T
F F
P ⇔Q
(P ⇐ Q) ∧ (P ⇒ Q),
i.e., P ⇔ Q ≡ (P ⇐ Q) ∧ (P ⇒ Q).
Let’s fill in its truth table.
P Q P ⇒Q P ⇐Q P ⇔Q
T T
T F
F T
F F
An implication and its friends
P Q P ⇒Q Q⇒P ¬Q ⇒ ¬P
T T
T F
F T
F F
(∀x ∈ A)E(x).
∀n ∈ Z, C(n) ⇔ P (n),
(∀x ∈ Z+ )P (x).
How can we show that this is false?
When showing that a universally quantified proposition is false, we
need to show “one” counter example. In this case, since P (4) is
false, ∀xP (x) is false.
This way of disproving a statement is equivalent to showing that
(∃x)(¬P (x)).
Negations of quantified propositions (2)
(∃x ∈ Z+ )Q(x).
How can we show that this is false?
When showing that an existential quantified proposition is false, we
need to show that Q(x) is false for every possible values of x. In
this case, since x2 = x · x > 2 · x for every x > 2, we have that
(∃x)Q(x) is false.
This way of disproving a statement is equivalent to showing that
(∀x)(¬Q(x)).
Negations of quantified propositions (3)